2011
DOI: 10.1074/jbc.m111.246850
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA Protein Phosphorylation Is Regulated by Mitotic Kinase Aurora and Protein Phosphatase 1

Abstract: Recent genetic studies in Drosophila identified Kibra as a novel regulator of the Hippo pathway, which controls tissue growth and tumorigenesis by inhibiting cell proliferation and promoting apoptosis. The cellular function and regulation of human KIBRA remain largely unclear. Here, we show that KIBRA is a phosphoprotein and that phosphorylation of KIBRA is regulated in a cell cycle-dependent manner with the highest level of phosphorylated KIBRA detected in mitosis. We further demonstrate that the mitotic kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
114
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(120 citation statements)
references
References 84 publications
6
114
0
Order By: Relevance
“…Plasmids-The human KIBRA, Mst1, Lats1, Lats2, Aurora-A, and Aurora-B constructs and their corresponding derivatives have been described previously (27,40). Truncated constructs were made by PCR and verified by sequencing and restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids-The human KIBRA, Mst1, Lats1, Lats2, Aurora-A, and Aurora-B constructs and their corresponding derivatives have been described previously (27,40). Truncated constructs were made by PCR and verified by sequencing and restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we showed that KIBRA is phosphorylated by Aurora-A and -B kinases during mitosis (40). Functions of Aurora kinases and Lats2 in mitosis are well defined, but whether KIBRA has a mitotic role is currently unknown.…”
mentioning
confidence: 97%
“…In Vitro Dephosphorylation/Phosphatase Assay-GST-YAP was first phosphorylated by CDK1/cyclin B in vitro as described (30). Phosphorylated GST-YAP was pulled down by glutathioneagarose (Santa Cruz Biotechnology, Dallas, TX), and the dephosphorylation assay was performed as previously described except 32 P was replaced by the phospho-antibodies (30).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylated GST-YAP was pulled down by glutathioneagarose (Santa Cruz Biotechnology, Dallas, TX), and the dephosphorylation assay was performed as previously described except 32 P was replaced by the phospho-antibodies (30). Antibodies, Immunoprecipitation, and Western Blot AnalysisThe YAP antibodies from Abnova (Taipei, Taiwan; catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation